PENGARUH PENYULUHAN KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS MUARA SATU KOTA LHOKSEUMAWE - Marlina Marlina; Aida Fitriani; Yusni Daryani; Lisni Lisni (Jurnal Medikes (Media Informasi Kesehatan), 2023)
The Exclusive Breastfeeding program promotes the only breastfeeding administration for the baby for the first 6 (six) months without adding and changing the breastfeeding with other kinds of food and drink. Based on the coverage of the Exclusive Breastfeeding Administration at Puskesmas (Community Health Center) Muara Satu in 2013, which was 44.6%, the media of health promotion done to change pregnant mothers' behavior was the lecture method with leaflet distribution. The purpose of this quasi-experimental study was to find out the influence of health promotion through the lecture method with the media of leaflets on the knowledge and attitude of pregnant mothers in Exclusive Breastfeeding Administration in the working area of Puskesmas Muara Satu, the city of Lhokseumawe in 2020. The population of the quasi-experimental study was 156 pregnant mothers living in the working area of Puskesmas Muara Satu in June 2020. The samples for this study were 25 pregnant mothers for the case/treatment group carried out in Desa Blang Pulo, and 25 pregnant mothers for the control group in Desa Batuphat Barat. The samples were selected through a purposive sampling method from the village under the criteria that in the village lived 25 pregnant mothers. The data obtained for this study with a non-randomized control group pretest post-test design were analyzed through the Independent t-test method. This study showed that there was an influence of health extension through the lecture method with the media of leaflets to improve the score of knowledge and attitude of pregnant mothers on the Exclusive Breastfeeding Administration with p-value = 0.001 < 0.05. The Head of Lhokseumawe Municipal Health Service is suggested to provide continuous training in Training of Trainer (TOT). The health extension workers should be more active in educating pregnant mothers about the Exclusive Breastfeeding Administration.